Casos de fraudes corporativas financeiras: antecedentes, recursos substantivos e simbólicos relacionados - Costa, Ana Paula Paulino da (2011)
Current management literature about corporate fraud usually is too fragmented considering the phenomena as an event. This fragmentation on organization study field has been cited as a limitation for comprehension and analysis of the complex theme (ASHFORTH et al., 2008), as neglecting that each type of fraud requires different set of resources, cognitive frames and contexts (BAUCUS, 1994; MACLEAN, 2008; MISANGYI; WEAVER; ELMS, 2008). This study aims to contribute to literature considering corporate fraud as a process, in an integrative (among levels of analysis) and interacionism (substantive and symbolic aspects) model. Adopting a research approach based on grounded theory, this study analyzed two emblematic cases of financial corporate fraud in Brazil in different segment: Boi Gordo (agrobusiness) and Banco Santos (banking). This resulted on a substantive knowledge on intentional financial corporate fraud context. Through document and discourses analysis this work studied the movement of the phenomenon, its origin, development, consolidation and crisis, what allowed identifying the characteristics (antecedents, substantive and symbolic aspects) of this type of fraud; how these elements are integrated (including the link between antecedents and modus operandi) and how the context was prepared for it (how resources gained new meanings). These procedures allowed apprehending the constitutive elements of this fraud process. These elements were also linked to social dimension aspects (DEBORD, 1997; BOORSTIN, 1992; GOFFMAN, 1959; BAUDRILLARD, 1991; BOURDIEU, 2007). It resulted on new theoretical elements applied to substantive context of intentional financial corporate fraud as the central one: ‘trust-based business’. This category integrates other aspects as the use of culture social values to access target public. It was also possible to identify how behavior changes along the process of fraud, identifying three moments: ‘origin’, ‘pseudo-coherence’, when business growth; and ‘spiral’, when business advance to bankruptcy. These results can be applied in future researches on other substantive contexts of fraud to construct more general theory and even to reformulate formal fraud corporate current theories.